PENGARUH MODEL QUIZ TEAM TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 18 BONTOKADATTO KAB. TAKALAR - Nur Hani Fadillah. S; Andi Husniati; A. Alim Syahri (STKIP Subang, 2025)
This study aims to determine the effect of the quiz team model on the motivation and mathematics learning outcomes of fifth grade students of SDN 18 Bontokadatto, Takalar Regency. The approach to this study is a quantitative approach with the type of Pre-Experimental Design research in the form of one group pretest-posttest. The subjects in this study were fifth grade students with a total of 15 students. The research instruments used in this study were observation sheets, learning outcome tests and motivation questionnaires. The data analysis techniques used were descriptive data analysis techniques and inferential data analysis. The results of the inferential statistical data analysis using the t-test, it is known that the t count value = 4.724 while the t table value = 1.671 at a significant level of ???? = 0.05. Based on these values, T count> T table is obtained, this means that H0 is rejected and H1 is accepted. From these results it is shown that there is an effect of the quiz team model on students' mathematics learning outcomes. On the student observation sheet during learning, there is a high level of learning activity for each indicator with an average percentage of 75% and on the student motivation questionnaire during learning, there are very positive respondents so that they have a high level of motivation with an average percentage of 80%. Based on these results, it can be concluded that there is an influence of the quiz team model on the motivation and mathematics learning outcomes of class V students of SDN 18 Bontokadatto, Takalar Regency